Potential short-term effects of earthquake on the plant–soil interface in alpine grassland of the Qinghai–Tibetan Plateau - Zuo, Hui; Shen, Hao; Dong, Shikui; Wu, Shengnan; He, Fengcai; Zhang, Ran; Wang, Ziying; Shi, Hang; Hao, Xinghai; Tan, Youquan; Ma, Chunhui; Li, Shengmei; et al. (Frontiers in Plant Science, 2023)
Earthquakes are environmental disturbance affecting ecosystem functioning, health, and biodiversity, but their potential impacts on plant-soil interface are still poorly understood. In this study, grassland habitats in areas near and away from the seismo-fault in Madou, a region typical of alpine conditions on the Qinghai-Tibetan Plateau, were randomly selected. The impacts of earthquake on soil properties and plant nutrient content in the short term were emphasized, and their potential relationships with community diversity and productivity were examined. According to the findings of the study, the Maduo earthquake led to a decrease in soil nutrient content in alpine grassland ecosystems, especially soil TC, TN, TP, TCa, AP, AK, NH4 + -N and SOC, and inhibited the absorption of N, Ca and Mg nutrients by plants. In addition, the diversity and productivity of communities were affected by both direct and indirect earthquake pathways. The negative impacts of seismic fracture on soil structure had the most significant direct impact on plant community diversity. Earthquake also indirectly reduced community productivity by 2 reducing the soil N content and inhibiting the absorption of plant nutrients. Our findings suggested that earthquake could potentially decrease the stability of the alpine grassland ecosystem on the QTP by affecting nutrient availability at the plant-soil interface.